The Impact of Alternative Learning System in Cotabato Division: A Case Study (International Journal of Scientific Research and Management (IJSRM), 2022)
As a result of the world Declaration of Education for All (EFA) in 1990, the Philippines designed Alternative Learning System (ALS), a program that will provide non-formal education to out-of-school children (OSC), out-of-school youth (OSY), illiterate adults and marginalized Filipinos that will address illiteracy and promote continuing education. This research study used the qualitative research design involving the Cotabato Division in the province of North Cotabato implementing the ALS A&E program. The mobile teachers. District ALS program coordinators , ALS A&E passers, and the division ALS program supervisors were the respondents of this study . The studies were conducted in Cotabato Division particularly Central Elementary Schools. It was concluded that the ALS program was successful in providing basic learning needs to its beneficiaries and most of them pass the A&E test and were able to obtain an elementary or high school diploma and even college degree.The Alternative System Program of the Department of Education has great impact in Social and Economic Development of the North Cotabato Province.